Exponents Rules - Examples, Exercises and Solutions

Question Types:
Applying Combined Exponents Rules: Applying the formulaApplying Combined Exponents Rules: Calculating powers with negative exponentsApplying Combined Exponents Rules: Complete the equationApplying Combined Exponents Rules: converting Negative Exponents to Positive ExponentsApplying Combined Exponents Rules: Factoring Out the Greatest Common Factor (GCF)Applying Combined Exponents Rules: FactorizationApplying Combined Exponents Rules: Identify the greater valueApplying Combined Exponents Rules: More than one unknownApplying Combined Exponents Rules: Multiplying Exponents with the same baseApplying Combined Exponents Rules: Number of termsApplying Combined Exponents Rules: A power lawApplying Combined Exponents Rules: Presenting powers in the denominator as powers with negative exponentsApplying Combined Exponents Rules: Presenting powers with negative exponents as fractionsApplying Combined Exponents Rules: Presenting powers with negative exponents as fractionsApplying Combined Exponents Rules: MonomialApplying Combined Exponents Rules: Single VariableApplying Combined Exponents Rules: TrinomialApplying Combined Exponents Rules: BinomialApplying Combined Exponents Rules: Two VariablesApplying Combined Exponents Rules: Using laws of exponents with parametersApplying Combined Exponents Rules: Using multiple rulesApplying Combined Exponents Rules: Using the laws of exponentsApplying Combined Exponents Rules: Using variablesApplying Combined Exponents Rules: Variable in the base of the powerApplying Combined Exponents Rules: Variable in the exponent of the powerApplying Combined Exponents Rules: Variables in the exponent of the powerApplying Combined Exponents Rules: Worded problemsApplying Combined Exponents Rules: The power of zero

Definition of Exponentiation

Exponents are a way to write the multiplication of a term by itself several times in a shortened form.

The number that is multiplied by itself is called the base, while the number of times the base is multiplied is called the exponent.

A - Exponentiation

an=aaa a^n=a\cdot a\cdot a ... (n times)

For example:

5555=54 5\cdot5\cdot5\cdot5=5^4

5 5 is the base, while 4 4 is the exponent.

In this case, the number 5 5 is multiplied by itself 4 4 times and, therefore, it is expressed as 5 5 to the fourth power or 5 5 to the power of 4 4 .

Practice Exponents Rules

Examples with solutions for Exponents Rules

Exercise #1

Solve the following problem:

(34)×(32)= \left(3^4\right)\times\left(3^2\right)=

Video Solution

Step-by-Step Solution

In order to solve this problem, we'll follow these steps:

  • Step 1: Identify the base and exponents

  • Step 2: Use the formula for multiplying powers with the same base

  • Step 3: Simplify the expression by applying the relevant exponent rule

Now, let's work through each step:

Step 1: The given expression is (34)×(32) (3^4) \times (3^2) . Here, the base is 3, and the exponents are 4 and 2.

Step 2: Apply the exponent rule, which states that when multiplying powers with the same base, we add the exponents:
am×an=am+n a^m \times a^n = a^{m+n}

Step 3: Using the rule identified in Step 2, we add the exponents 4 and 2:
34×32=34+2=36 3^4 \times 3^2 = 3^{4+2} = 3^6

Therefore, the simplified form of the expression is 36 3^6 .

Answer

36 3^6

Exercise #2

2423= \frac{2^4}{2^3}=

Video Solution

Step-by-Step Solution

Let's keep in mind that the numerator and denominator of the fraction have terms with the same base, therefore we use the property of powers to divide between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it in the problem:

2423=243=21 \frac{2^4}{2^3}=2^{4-3}=2^1 Remember that any number raised to the 1st power is equal to the number itself, meaning that:

b1=b b^1=b Therefore, in the problem we obtain:

21=2 2^1=2 Therefore, the correct answer is option a.

Answer

2 2

Exercise #3

Simplify the following equation:

53×24×52×23= 5^3\times2^4\times5^2\times2^3=

Video Solution

Step-by-Step Solution

Let's simplify the expression 53×24×52×23 5^3 \times 2^4 \times 5^2 \times 2^3 using the rules for exponents. We'll apply the product of powers rule, which states that when multiplying like bases, you can add the exponents.

  • Step 1: Focus on terms with the same base.
    Combine 53 5^3 and 52 5^2 . Since both terms have the base 55, we apply the rule am×an=am+na^m \times a^n = a^{m+n}: 53×52=53+2=55 5^3 \times 5^2 = 5^{3+2} = 5^5

  • Step 2: Combine 24 2^4 and 23 2^3 . Similarly, for the base 22: 24×23=24+3=27 2^4 \times 2^3 = 2^{4+3} = 2^7

After simplification, the expression becomes:
55×27 5^5 \times 2^7

Answer

55×27 5^5\times2^7

Exercise #4

9993= \frac{9^9}{9^3}=

Video Solution

Step-by-Step Solution

Note that in the fraction and its denominator, there are terms with the same base, so we will use the law of exponents for division between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} Let's apply it to the problem:

9993=993=96 \frac{9^9}{9^3}=9^{9-3}=9^6 Therefore, the correct answer is b.

Answer

96 9^6

Exercise #5

Reduce the following equation:

a2×a5×a3= a^2\times a^5\times a^3=

Video Solution

Step-by-Step Solution

To reduce the expression a2×a5×a3 a^2 \times a^5 \times a^3 , we will apply the product of powers property of exponents. This property states that when multiplying expressions with the same base, we add their exponents.

  • Step 1: Identify the exponents.
    The expression involves the same base a a with exponents: 2, 5, and 3.
  • Step 2: Add the exponents.
    According to the product of powers property, a2×a5×a3=a2+5+3 a^2 \times a^5 \times a^3 = a^{2+5+3} .
  • Step 3: Simplify the expression.
    Calculate the sum of the exponents: 2+5+3=10 2 + 5 + 3 = 10 . Therefore, the expression simplifies to a10 a^{10} .

Ultimately, the solution to the problem is a10 a^{10} . Among the provided choices, is correct: a10 a^{10} . The other options a5 a^5 , a8 a^8 , and a4 a^4 do not correctly reflect the sum of the exponents as calculated.

Answer

a10 a^{10}

Exercise #6

Simplify the following equation:

64×23×62×25= 6^4\times2^3\times6^2\times2^5=

Video Solution

Step-by-Step Solution

To simplify the equation 64×23×62×25 6^4 \times 2^3 \times 6^2 \times 2^5 , we will make use of the rules of exponents, specifically the product of powers rule, which states that when multiplying two powers that have the same base, you can add their exponents.

Step 1: Identify and group the terms with the same base.
In the expression 64×23×62×25 6^4 \times 2^3 \times 6^2 \times 2^5 , group the powers of 6 together and the powers of 2 together:

  • Powers of 6: 64×62 6^4 \times 6^2

  • Powers of 2: 23×25 2^3 \times 2^5

Step 2: Apply the product of powers rule.
According to the product of powers rule, for any real number a a , and integers m m and n n , the expression am×an=am+n a^m \times a^n = a^{m+n} .

Apply this rule to the powers of 6:
64×62=64+2=66 6^4 \times 6^2 = 6^{4+2} = 6^6 .

Apply this rule to the powers of 2:
23×25=23+5=28 2^3 \times 2^5 = 2^{3+5} = 2^8 .

Step 3: Write down the final expression.
Combining our results gives the simplified expression: 66×28 6^6 \times 2^8 .

Therefore, the solution to the problem is 66×28 6^6 \times 2^8 .

Answer

66×28 6^6\times2^8

Exercise #7

Insert the corresponding expression:

(x3)4= \left(x^3\right)^4=

Video Solution

Step-by-Step Solution

To simplify the expression (x3)4 (x^3)^4 , we'll follow these steps:

  • Step 1: Identify the expression: (x3)4 (x^3)^4 .
  • Step 2: Apply the formula for a power raised to another power.
  • Step 3: Calculate the product of the exponents.

Now, let's work through each step:

Step 1: We have the expression (x3)4 (x^3)^4 , which involves a power raised to another power.

Step 2: We apply the exponent rule (am)n=amn(a^m)^n = a^{m \cdot n} here with a=xa = x, m=3m = 3, and n=4n = 4.

Step 3: Multiply the exponents: 3×4=12 3 \times 4 = 12 . This gives us a new exponent for the base x x .

Therefore, (x3)4=x12(x^3)^4 = x^{12}.

Consequently, the correct answer choice is: x12 x^{12} from the options provided. The other options x6 x^6 , x1 x^1 , and x7 x^7 do not reflect the correct application of the exponent multiplication rule.

Answer

x12 x^{12}

Exercise #8

Simplify the following equation:

42×35×43×32= 4^2\times3^5\times4^3\times3^2=

Video Solution

Step-by-Step Solution

To simplify the given expression 42×35×43×32 4^2 \times 3^5 \times 4^3 \times 3^2 , we will follow these steps:

  • Step 1: Identify and group similar bases.

  • Step 2: Apply the rule for multiplying like bases.

  • Step 3: Simplify the expression.

Now, let's go through each step thoroughly:

Step 1: Identify and group similar bases:
We see two distinct bases here: 4 and 3.

Step 2: Apply the rule for multiplying like bases:
For base 4: Combine 424^2 and 434^3, using the rule am×an=am+na^m \times a^n = a^{m+n}.

Add the exponents for base 4: 2+3=5 2 + 3 = 5 , thus, 42×43=45 4^2 \times 4^3 = 4^5 .

For base 3: Combine 353^5 and 323^2, still using the same exponent rule.

Add the exponents for base 3: 5+2=7 5 + 2 = 7 , resulting in 35×32=37 3^5 \times 3^2 = 3^7 .

Step 3: Simplify the expression:
The simplified expression is 45×37 4^5 \times 3^7 .

Therefore, the final simplified expression is 45×37 4^5 \times 3^7 .

Answer

45×37 4^5\times3^7

Exercise #9

(43)2= (4^3)^2=

Step-by-Step Solution

To solve (43)2 (4^3)^2 , we use the power of a power rule which states that (am)n=amn (a^m)^n = a^{m \cdot n} .

Here, a=4 a = 4 , m=3 m = 3 , and n=2 n = 2 .

So, we calculate 432 4^{3 \cdot 2} ,

which simplifies to 46 4^6 .

Answer

46 4^6

Exercise #10

(35)4= (3^5)^4=

Video Solution

Step-by-Step Solution

To solve the exercise we use the power property:(an)m=anm (a^n)^m=a^{n\cdot m}

We use the property with our exercise and solve:

(35)4=35×4=320 (3^5)^4=3^{5\times4}=3^{20}

Answer

320 3^{20}

Exercise #11

Insert the corresponding expression:

y9y3= \frac{y^9}{y^3}=

Video Solution

Step-by-Step Solution

To solve the expression y9y3\frac{y^9}{y^3}, we will apply the rules of exponents, specifically the power of division rule, which states that when you divide like bases, you subtract the exponents.


Here are the steps to arrive at the solution:

  • Step 1: Identify and write down the expression: y9y3\frac{y^9}{y^3}.

  • Step 2: Apply the division rule of exponents, which is aman=amn\frac{a^m}{a^n} = a^{m-n}, for any non-zero base aa.

  • Step 3: Using the division rule, subtract the exponent in the denominator from the exponent in the numerator:y93 y^{9-3}

  • Step 4: Calculate the exponent: 93=6 9 - 3 = 6

  • Step 5: Write down the simplified expression:y6 y^6

Therefore, the expression y9y3\frac{y^9}{y^3} simplifies to y6 y^6 .

Answer

y6 y^6

Exercise #12

(23)6= (2^3)^6 =

Step-by-Step Solution

To solve the given expression (23)6 (2^3)^6 , we apply the power of a power rule (am)n=amn (a^m)^n = a^{m \cdot n} . Here, a=2 a = 2 , m=3 m = 3 , and n=6 n = 6 .

Thus, we calculate the exponent:

36=18 3 \cdot 6 = 18

So, (23)6=218 (2^3)^6 = 2^{18} .

Answer

218 2^{18}

Exercise #13

Insert the corresponding expression:

x6x4= \frac{x^6}{x^4}=

Video Solution

Step-by-Step Solution

To solve the given expression x6x4 \frac{x^6}{x^4} , we will follow these steps:

  • Step 1: Apply the quotient rule for exponents
  • Step 2: Simplify the expression
  • Step 3: Verify by comparing with the answer choices

Now, let's work through each step:

Step 1: Apply the quotient rule for exponents. This rule states that aman=amn \frac{a^m}{a^n} = a^{m-n} when dividing powers with the same base.

Step 2: We have x6x4 \frac{x^6}{x^4} . According to the rule:

x6x4=x64=x2 \frac{x^6}{x^4} = x^{6-4} = x^2

Step 3: Verify by comparing with the answer choices:

  • Choice 1: x2 x^{-2} – Incorrect as it implies the exponents were added incorrectly.
  • Choice 2: x2 x^2 – This matches our result.
  • Choice 3: x10 x^{10} – Incorrect as it implies the exponents were added instead of subtracted.
  • Choice 4: x23 x^{\frac{2}{3}} – Incorrect as it does not match the calculation based on integer exponents.

Therefore, the correct choice is x2 x^2 , which is Choice 2.

Answer

x2 x^2

Exercise #14

Solve the following problem:

70= 7^0=

Video Solution

Step-by-Step Solution

To solve the problem of finding 70 7^0 , we will follow these steps:

  • Step 1: Identify the general rule for exponents with zero.

  • Step 2: Apply the rule to the given problem.

  • Step 3: Consider the provided answer choices and select the correct one.

Now, let's work through each step:

Step 1: A fundamental rule in exponents is that any non-zero number raised to the power of zero is equal to one. This can be expressed as: a0=1 a^0 = 1 where a a is not zero.

Step 2: Apply this rule to the problem: Since we have 70 7^0 , and 7 7 is certainly a non-zero number, the expression evaluates to 1. Therefore, 70=1 7^0 = 1 .

Therefore, the solution to the problem is 70=1 7^0 = 1 , which corresponds to choice 2.

Answer

1 1

Exercise #15

Solve the following problem:

(3)0= \left(-3\right)^0=

Video Solution

Step-by-Step Solution

To solve this problem, let's follow these steps:

  • Understand the zero exponent rule.

  • Apply this rule to the given expression.

  • Identify the correct answer from the given options.

According to the rule of exponents, any non-zero number raised to the power of zero is equal to 11. This is one of the fundamental properties of exponents.
Now, apply this rule:

Step 1: We are given the expression (3)0(-3)^0.
Step 2: Here, 3-3 is our base. We apply the zero exponent rule, which tells us that (3)0=1(-3)^0 = 1.

Therefore, the value of (3)0(-3)^0 is 11.

Answer

1 1